Efficacy and safety of glue mesh fixation for laparoscopic inguinal hernia: A meta-analysis of randomized controlled trials - Nan Hu; Hong Xie; Deng-Chao Wang; Yue-Hua Lei; Jian Wei; Miao Yu; Yue-Juan Li (Asian Journal of Surgery, 2023)
It is still controversial whether glue can be used for mesh fixation in laparoscopic inguinal hernia repair. The aim of this meta-analysis was used to systematically evaluate the effectiveness and safety of glue mesh fixation in laparoscopic tension-free inguinal hernia repair. The PubMed database, EMBASE database and Cochrane Library were searched to collect published randomized controlled trials (RCTs) on laparoscopic tension-free inguinal hernia repair with glue mesh fixation. Sixteen RCTs and 2409 patients with inguinal hernia were included. The meta-analysis showed that compared with the mechanical mesh fixation group(MMFG), the glue mesh fixation group(GMFG) had significantly reduced incidences of chronic pain[relative risk (RR) = 0.40, 95% confidence interval (CI) (0.28,0.57), P < 0.00001], urinary retention[RR = 0.53, 95% CI(0.29,0.97), P = 0.04], haematoma[RR = 0.23, 95% CI(0.09,0.58), P = 0.002] and total complications[RR = 0.28, 95% CI(0.18,0.44), P < 0.00001]; there were no significant differences in pain score on postoperative day 1[MD = −1.33, 95% CI(-2.93,0.26), P = 0.10], operation time[MD = 1.46, 95% CI(-3.97,6.88), P = 0.60] and recurrence rate[RR = 0.72, 95% CI(0.35,1.47), P = 0.37] between the two groups. In conclusion, the application of glue mesh fixation in laparoscopic inguinal hernia repair is safe and reliable with fewer complications. Moreover, it can reduce the incidence of chronic pain without increasing the recurrence rate. However, due to the small number of cases in this analysis and limitations in the quality of the included studies, the findings need to be further verified by multicentre, large-sample and high-quality RCTs in the future.